Analysis of Small Aircraft Types and their Accidents in the Czech Republic - Endrizalová, Eva; Němec, Vladimír; Novák, Martin; Mrázek, Petr (Kaunas University of Technology, 2019)
The share of investigated small aircraft accidents in all air accidents in the Czech Republic is 1/3. The analysis was carried out within the project of the Ministry of the Interior - Simulation of the Firefighters Interventions during Air Accidents. The first objective of the analysis was to create a catalogue of all types of small aircraft operated in the Czech Republic and to determine the number of these aircraft according to the types in selected categories. The second objective was to analyze the accidents of small aircraft that have occurred in the Czech Republic during the last 12 years and to bring forth the results which are important from the point of view of firefighters' interventions.
Analýza typů malých letadel a jejich nehod v České republice
Keywords: Accidents; Aircraft register; ECCAIRS; Small aircraft; Ultralight; Nehoda; registr; ECCAIRS; malá letadla; ultralight